Decentralized Finance Unmasked Behavioral Finance and Public Policy Insights on Financial Market Regulation - Bergt, Josef (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Decentralized finance (DeFi) is a form of finance without central financial intermediaries. This handbook explores the interplay of behavioral finance and public policy in the emerging field of decentralized finance. The work explaines the underlying mechanisms in a nutshell from a social science, economics and legal perspective investigates DeFi's potential impact on financial systems and the risks involved, including smart contract vulnerabilities and trust mechanisms. provides insights into financial decision-making processes in DeFi offers suggestions to enhance regulatory frameworks.